Implementasi Pembelajaran Berdiferensiasi Produk Berdasarkan Gaya Belajar Untuk Meningkatkan Kreativitas Peserta Didik Mata Pelajaran Sejarah di SMA Negeri 2 Palembang - Rizka Setya Rini, Hudaidah, Wardiyah (LP4MK STKIP PGRI Lubuklinggau, 2026)
Education is a humanizing proses that shapes individual character and skills, contributing to society. In the 21st century education era, the main focus is on cognitive, affective and psychomotor abilities. Adaptive learning approaches, such as differentiated learning, are important to meet the needs of each learner’s unique learning style, including visual, auditory, and kinesthetic. This research uses the PTK (Classroom Action Research) method to evaluate product differentiated learning in class XI SMA Negeri 2 Palembang, especially on the material of the VOC Triumph Period. The results showed that the application of the Project Based Learning model adapted to the learning style of students significantly increased the creativity of students from 23% initially to 91% in the second cycle. This shows that PjBL based on product differentiation is effective in increasing the creativity of students.